The Role of Information and Communication Technology in EFL Students Writing Creativity Development - Iin Anggeriani; Andi Sadapotto; Ibrahim Manda; Sam Hermansyah (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2024)
This study used a qualitative research approach. This research aims to find out how students see the role of information and communication technology in improving writing creativity. The researcher gathered 8 4th semester English students at Universitas Muhammadiyah Sidenreng Rappang. The researcher collected data through questionnaires and interviews. This is evidenced by the percentage of 50% of the total frequency of 4 out of 8 students who strongly agree that the existence of information and communication technology can improve writing creativity. The percentage who agree with the existence of information and communication technology can improve writing creativity is 37.5% with 3 students, and the percentage who disagree with the existence of information and communication technology can improve writing creativity is 12.5% with 1 student, and there are no students who strongly disagree with the existence of information and communication technology can develop writing creativity.